Brief Experimental Analysis of Reading Deficits for Children With Attention-Deficit/Hyperactivity Disorder. (January 2015) - Fienup, Daniel M.; Reyes-Giordano, Kimberly; Wolosik, Katarzyna; Aghjayan, Anto; Chacko, Anil
Reading difficulties are especially high among children with attention-deficit/hyperactivity disorder (ADHD). Although there are a number of empirically supported reading interventions for children with ADHD, there is little data to guide the selection of the most efficacious reading intervention for a specific child. Brief experimental analysis (BEA) is a procedure that directly compares the efficacy of various academic interventions with the goal of guiding the selection of the intervention that results in optimal efficacy. The current proof of concept study examined the efficacy of the BEA methodology for determining the relative effectiveness of seven reading interventions for children with ADHD. The seven interventions included empirically supported ADHD interventions as well as traditional interventions found in the BEA literature. Six children diagnosed with ADHD completed the proof of concept study. Results indicated that the BEA successfully determined an efficacious intervention for each participant. The efficacy of the interventions and the optimal intervention based on BEA procedures varied for each child, suggesting the importance of a BEA approach when comparing various interventions for reading in children with ADHD. Implications and future directions for selecting effective reading interventions for children with ADHD are discussed.